2009
DOI: 10.1088/0004-637x/691/1/152
|View full text |Cite
|
Sign up to set email alerts
|

HIGH-REDSHIFT STARBURSTING DWARF GALAXIES REVEALED BY Γ-Ray BURST AFTERGLOWS

Abstract: We present a study of 15 long-duration γ-ray burst (GRB) host galaxies at z > 2. The GRBs are selected with available early-time afterglow spectra in order to compare interstellar medium (ISM) absorption-line properties with stellar properties of the host galaxies. In addition to five previously studied hosts, we consider new detections for the host galaxies of GRB 050820 and GRB 060206 and place 2-σ upper limits to the luminosities of the remaining unidentified hosts. We examine the nature of the host galaxy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
112
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(126 citation statements)
references
References 135 publications
14
112
0
Order By: Relevance
“…This hypothesis could be also supported by the results recently obtained by (Chen et al 2009). These authors analyzed 7 GRB fields and found the presence of at least one addition object at angular separation from the GRB afterglow position in all the four fields of GRBs with known intervening strong MgII galaxies.…”
Section: Resultssupporting
confidence: 85%
“…This hypothesis could be also supported by the results recently obtained by (Chen et al 2009). These authors analyzed 7 GRB fields and found the presence of at least one addition object at angular separation from the GRB afterglow position in all the four fields of GRBs with known intervening strong MgII galaxies.…”
Section: Resultssupporting
confidence: 85%
“…They are also considered to be the building blocks of much larger and more metalrich galaxies (Review by Tosi 2003). They also show analogies with Gamma Ray Bursts (GRB) hosts whose ISM usually exhibit moderate chemical enrichment with a median metallicity of 1/10 Z (Chen et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…So far, there are only eight bursts with z > 3 where the detection of a host galaxy has been published, namely GRB 971214 (z = 3.418, Kulkarni et al 1998), GRB 000131 (z = 4.500, Andersen et al 2000;Fruchter et al 2006), GRB 030323 (z = 3.3718, Vreeswijk et al 2004), GRB 060206 (z = 4.04795, Fynbo et al 2006;Thöne et al 2008;Chen at al. 2009), GRB 060210 (z = 3.9133, Fynbo et al 2009;Perley et al 2009), GRB 060605 (z = 3.773, Ferrero et al 2009), GRB 090205 (z = 4.6503, D'Avanzo et al 2010, and GRB 090323 (z = 3.568, Cenko et al 2010;McBreen et al 2010).…”
Section: Host Searchmentioning
confidence: 99%
“…2009), GRB 060210 (z = 3.9133, Fynbo et al 2009;Perley et al 2009), GRB 060605 (z = 3.773, Ferrero et al 2009), GRB 090205 (z = 4.6503, D'Avanzo et al 2010, and GRB 090323 (z = 3.568, Cenko et al 2010;McBreen et al 2010). The host galaxies of GRB 020124 (Berger et al 2002;Chen at al. 2009), GRB 050730, GRB 050908, GRB 060607A, GRB 070721B (all Chen at al.…”
Section: Host Searchmentioning
confidence: 99%
See 1 more Smart Citation